Effect of copper ions on the flotation separation of chalcopyrite and molybdenite using sodium sulfide as a depressant. (January 2018) - Zhao, Qiang; Liu, Wengang; Wei, Dezhou; Wang, Wendan; Cui, Baoyu; Liu, Wenbao
Graphical abstract: Highlights: Copper ions severely deteriorate the floatability of chalcopyrite and molybdenite. The adsorption of CuOH + and Cu(OH)2 provide more reaction sites for depressants. Cu2 S is identified as the primary product during the inhibition process. The similar floatability makes it difficult to achieve Cu-Mo flotation separation. An inhibition model among mineral surface, copper ions and sulfide ions is proposed. Abstract: Copper ions are unavoidable in the process of copper-molybdenum flotation separation. The flotation response of chalcopyrite and molybdenite in the presence of copper ions was investigated through single mineral flotation tests and flotation separation tests. The influence mechanism was studied by adsorption experiments, zeta-potential measurements, and X-ray photoelectron spectroscopy (XPS) analysis. Flotation results indicated that copper ions dramatically reduced the recoveries of copper and molybdenum, and increased the inhibition effect of sodium sulfide; that is, the flotation separation of chalcopyrite and molybdenite was seriously hindered by copper ions. The adsorption experiments demonstrated that copper ions were adsorbed on molybdenite and chalcopyrite, and the adsorption amounts increased in the presence of sodium sulfide. The results of zeta-potential measurements confirmed that the floatability of the minerals was deteriorated by the adsorption of copper hydroxides (Cu(OH) + and Cu(OH)2 ) and the subsequent adsorption of hydrosulfide ions (HS − ). Moreover, XPS analysis verified that the adsorbed copper hydroxides reacted with hydrosulfide ions, producing Cu(I)-S species on the surface of chalcopyrite and molybdenite. The adsorbed Cu(I) ions provided additional reaction sites and promoted the formation of a hydrophilic layer by the attachment of excessive hydrosulfide ions. Based on these analyses, a possible inhibition model for the interactions among the mineral surface, copper ions, and sulfide ions is proposed.